Conjugated linoleic acid in Bufalo (Bubalus bubalis) milk from Argentine - Van Nieuwenhove, Carina Paola (2004)
Conjugated linoleic acid (CLA), a naturally occurring anticarcinogen found in dairy products, has received increasing attention in recent years. Twelve lactating Murrah river buffaloes (Bubalus bubalis) were used to study profile long-chain fatty acids in milk fat. Buffaloes were fed with natural pasture ad libitum. Milk samples were collected in the morning. Animals were separated by stage lactation (3-4 months). The composition of milk samples and fatty acids profile was analyzed. Milk was refrigerated, homogenized and pasteurized for evaluating any possible effect of treatment on cis9, trans11 octadecadienoic acid (CLA) level. Results show that 59% of long chain fatty acids are saturated. C16:0 was the most abundant fatty acid in buffalo milk and C18:1 the major unsaturated fatty acid. CLA level in buffalo milk was 4.83 mg/g of fatty acid methyl ester (FAME). There was a positive correlation between CLA and trans-11 C18:1 vaccenic acid. Any treatment of buffalo raw milk modified significantly CLA content or other fatty acids. Milk fat content of trans11 C18:1 and CLA were closely related (r = 0.90). A high quality of buffalo milk was obtained after a diet based only on cultured of pasture carried out in Northwest Argentine.